Propagule pressure and genetic diversity enhance colonization by a ruderal species: a multi‐generation field experiment. Issue 3 (23rd May 2019) - Hovick, Stephen M.; Whitney, Kenneth D.
Abstract: Colonization is a critical filter, setting the stage for short‐term and long‐term population success. Increased propagule pressure (e.g., more founding individuals) usually enhances colonization; however, this pattern may be driven by purely numeric effects, population genetic diversity effects, or both. To determine the independent and interactive effects of propagule pressure and genetic diversity, we conducted a seed addition experiment in the field using the ruderal annual Arabidopsis thaliana . Propagule pressure treatments spanned five levels, from 32 to 960 seeds per 0.25‐m 2 plot. Founder populations were composed of one, four, or eight genotypes and exposed to ambient or reduced levels of interspecific competition. Genotype monocultures were included to quantify additive vs. non‐additive effects. Populations were followed for three generations, with abundance, population persistence and genotype retention (the proportion of introduced genotypes persisting over time) as the major response variables. Increased propagule pressure enhanced abundance immediately following introduction, particularly where nutrient availability was high and competition reduced. Greater propagule pressure also increased the likelihood of population persistence and genotype retention through three generations. However, most populations experienced rapid abundance declines over time, yielding no relationship between propagule pressure and third‐generation abundance across persisting populations. Under reduced competition, increased genetic diversity led to a marginal increase in persistence through the third generation that was more pronounced, and statistically significant, in low nutrient conditions. Genetic diversity did not affect persistence through the first generation, thus indicating that genetic diversity effects strengthened over time. Nevertheless, genotypic mixture populations fell short of expectations based on performance in monocultures (negative non‐additive effects). Increased genetic diversity was also associated with abundance declines, largely due to one particularly high‐performing genotype in the lowest diversity treatments (i.e., genotypic identity effects). Overall, our results indicate that increases in both propagule pressure and genetic diversity can enhance colonization success but are highly context dependent. They also highlight novel ways in which both factors can impact the retention of introduced genetic diversity over time. Our findings pinpoint the determinants of a fundamental population process and have key implications for applications where enhanced or suppressed colonization is desired, including ecological restoration and invasive species management.